1989
DOI: 10.1002/chin.198946279
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Arylferrocenyl‐1,3‐butadienes.

Abstract: Starting with the α,β‐unsaturated ketones (I), the title compounds (V) are prepared via the carbinols (III) and characterized as the adducts (VII) with maleic anhydride (VI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The mechanism of cationic cycloaddition to ferrocenylbuta-1,3-dienes and the effect of stereoelectronic factors have been studied in detail earlier. [9] It is noteworthy that cyclodimer 8 is formed as a single diastereomeric ( 1 H NMR data) despite the presence of three stereogenic centers. The physicochemical characteristics of compound 8 and 1 H NMR spectroscopic data totally coincide with those reported earlier.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The mechanism of cationic cycloaddition to ferrocenylbuta-1,3-dienes and the effect of stereoelectronic factors have been studied in detail earlier. [9] It is noteworthy that cyclodimer 8 is formed as a single diastereomeric ( 1 H NMR data) despite the presence of three stereogenic centers. The physicochemical characteristics of compound 8 and 1 H NMR spectroscopic data totally coincide with those reported earlier.…”
Section: Resultsmentioning
confidence: 98%
“…The physicochemical characteristics of compound 8 and 1 H NMR spectroscopic data totally coincide with those reported earlier. [9] Compounds 9 and 10 resulted from the classical 1,2-addition of methyllithium to the carbonyl group followed by dehydration of tertiary alcohols 16 and 17 in an acidic medium (Scheme 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mixtt, re was stirred at 20 ~ for 4 h. and 200 mL of water was added, l'he reaction products were extracted with benzene (3x50 mL). After the solvent had been evaporated it7 racuo, the residue was ehromatographed on AI20 ~ iusing benzene as the elnent) to give 0.22 g il I%) of 3,5-bisiferrocenylmethylene)-l-methyl-4-methylenepiperidine (3) Ferrocenylmethylene-3-( ferrocenylmethan-l-ylium-I-yl)-i,4-dimethyl-1,2,5,6-tetrahydropyridinium bis(tetrafluoroborate) ( Thermal cyclodimerization of triene 3. A solution of triene 3 {0.5 g. I mmot) in 50 mL of m-xylene was refluxcd for 4 h. After evaporation of the solvent in vacuo, the residue ,,,,as chromatographed on AI20 ) (using benzene as the eluem) to give (I.22 g (43%) of 8-ferrocenyl-4,3",5"-tris(ferrocenylmethy ene)-2 I "-dimeThvlspiro I 1, 2,3,4,5,6,7.8- …”
Section: Methodsmentioning
confidence: 99%
“…we found that diferrocenyltriene ..I is [brmed in a low yield even during the standard dehydration, of alcohol 5 on treatment with POCI:; in pyridine. 3 The major product formed in tile reaction was spiro cyclodimer ~6). …”
Section: Fc = Cshffecshmentioning
confidence: 99%